Long-term efficacy of surgical ablation of atrial fibrillation in a low-volume centre - Rachwalik, Maciej; Zyśko, Dorota; Bielicki, Grzegorz; Obremska, Marta; Goździk, Anna; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Surgical ablation is a recommended procedure for patients with atrial fibrillation (AF) undergoing a cardiac surgery operation. However, the procedure is associated with significant risk of late recurrence of AF. The aim of the study was to assess the long-term efficacy of the procedure with respect to the comorbidities. The study group consisted of 22 patients: 9 women and 13 men, who underwent surgical AF ablation in the 2008-2013 period. The patients were interviewed by telephone and were asked to send their recently performed 12-lead electrocardiography (ECG). The semi-structured interview consisted of 25 items regarding the history of AF, concomitant comorbidities, lifelong syncopal history, smoking, family history of premature cardiovascular diseases, and current medical treatment. Furthermore, the Epworth test was performed to measure the daytime sleepiness, which in turn is related to the presence of obstructive sleep apnoea. On the basis of the obtained data, the CHADS 2 , and Epworth scale scores were calculated for each patient. As a result of the study six patients (27%) had sinus rhythm or paced dual chamber rhythm, and 16 patients had atrial fibrillation. The multivariate analysis revealed that Epworth scale scoring > 9, CHADS 2 score > 0, and persistent type of AF were related to poor outcome of surgical ablation procedure. In conclusion, patients with AF treated with surgical ablation have similar prognosis of sinus rhythm maintenance to those treated with radiofrequency ablation. Moreover, the same predisposing factors play a significant role in AF recurrence both in surgical patients and in patients treated with radiofrequency ablation.